1997
DOI: 10.1161/01.hyp.29.1.242
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Dimethylarginine, an Endogenous Nitric Oxide Synthase Inhibitor, in Experimental Hypertension

Abstract: Nc,NG-dimethyl-L-argmme (ADMA) IS an endogenously synthesized mtnc oxide (NO) synthase mhibltor which has potent pressor/vasoconstnctor effects Dimethylargmmase metabolizes ADMA to L-citrullme and plays a key role m deterrmmng the m VIVO levels of ADMA To mvestlgate the role of ADMA m the pathogenesls of hypertension, we measured 24-hour urinary excretion of ADMA (UADMA) and nitrate/nitrite (NOx) m Dahl salt-sensitive hypertensive rats and spontaneously hypertensive rats (SHR) In Dahl salt-resistant rats, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
139
0
8

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(157 citation statements)
references
References 26 publications
9
139
0
8
Order By: Relevance
“…However, this dysfunction presents di erent characteristics depending on the model studied (Boulanger, 1999). In Dahl-salt sensitive rats, impaired eNOS activity (Hayakawa & Raij, 1997) and increased endogenous NOS inhibitor (Matsuoka et al, 1997) are associated with a decrease in endothelium-dependent relaxations. Furthermore, in large arteries from aged SHR, endothelium-dependent relaxations are impaired because of the concomitant augmented release of a contractile factor (LuÈ scher & Vanhoutte, 1986) and superoxide anions (Bauersachs et al, 1998).…”
Section: British Journal Of Pharmacology Vol 134mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this dysfunction presents di erent characteristics depending on the model studied (Boulanger, 1999). In Dahl-salt sensitive rats, impaired eNOS activity (Hayakawa & Raij, 1997) and increased endogenous NOS inhibitor (Matsuoka et al, 1997) are associated with a decrease in endothelium-dependent relaxations. Furthermore, in large arteries from aged SHR, endothelium-dependent relaxations are impaired because of the concomitant augmented release of a contractile factor (LuÈ scher & Vanhoutte, 1986) and superoxide anions (Bauersachs et al, 1998).…”
Section: British Journal Of Pharmacology Vol 134mentioning
confidence: 99%
“…In Dahl salt-sensitive hypertensive rats, a high salt diet has been shown to impair endothelium-dependent relaxations induced by a variety of vasodilators (LuÈ scher et al, 1987;Raij et al, 1988). This impairment is considered to be due to a decreased release of nitric oxide (NO) from the endothelium (Nava & LuÈ scher, 1995;Boegehold, 1992), which results from reduced endothelial NO synthase (eNOS) activity or increased endogenously synthesized NOS inhibitor (Hayakawa & Raij, 1997;Matsuoka et al, 1997). Similar impairment of NO synthesis and release by a high salt intake has been observed as a pathogenic factor in the development of hypertension in healthy subjects (Facchini et al, 1999) or normal Sprague-Dawley rats (Tolins & Shultz, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…DDAH I predominates in tissues that express the neuronal isoform of NOS, while DDAH II distribution mainly follows endothelial NOS (Leiper et al, 1999). Dysfunction of DDAH and elevated levels of its substrate ADMA have been implicated in pathological conditions including hypertension, pre-eclampsia, renal failure and atherosclerosis (Matsuoka et al, 1997;Holden et al, 1998;Miyazaki et al, 1999). Recently, high levels of ADMA have been correlated with impaired angiogenesis in hypercholesterolemic mice (Jang et al, 2000).…”
mentioning
confidence: 99%
“…A decreased plasma L-arginine to ADMA ratio or increased ADMA concentrations has been described in hypercholesterolemia [6,7], hypertension [8,9], arterial occlusive disease [10], chronic renal failure [11], and preeclampsia [12]. It has been suggested that alteration of the L-arginine to ADMA ratio could affect the clinical course of arteriosclerosis, which has not been seen in patients with stable angina [13].…”
mentioning
confidence: 99%